Verificação dos subsistemas de captor e descida do sistema de proteção contra descargas atmosféricas dos blocos da UTFPR Câmpus Medianeira - Castro, Jean Michael de (2014)
The lightning are made by passing electric current through the air. Due to the high dielectric strength of the air formation of rays takes place at high electric fields and electric current intensities causing, for this reason, malfunctions when they reach structures and may also cause people death. Thus several studies have been made regarding the form of protection and its effectiveness in buildings, are called Protection Systems Lightning (PSL). The buildings may have the SPDA installed on the mandatory or optional way, the definition by the installation of SPDA is by ABNT / NBR 5419/2005 and vary by region, the weather conditions and the occupation of the same, and other environmental conditions. In this sense the study was conducted of the need and conditions SPDA installed in blocks of UTFPR (Campus Medianeira). Through the construction and implementation of a checklist considering 40 items related to the standard sensors and descents which were found among the 20 blocks analyzed, 45% conforming items and 24.125% non-conforming items. The rest of the items listed in the standard (30.875%) do not apply to the analyzed blocks. The results of this study point to the importance of the management plan of maintenance of SPDA systems.